Toxoplasma gondii Impairs Myogenesis in vitro, With Changes in Myogenic Regulatory Factors, Altered Host Cell Proliferation and Secretory Profile - Vieira, Paloma de Carvalho; Waghabi, Mariana Caldas; Beghini, Daniela Gois; Predes, Danilo; Abreu, Jose Garcia; Mouly, Vincent; Butler-Browne, Gillian; Barbosa, Helene Santos; Adesse, Daniel (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii is the causative agent of toxoplasmosis, a parasitic disease with a wide global prevalence. The parasite forms cysts in skeletal muscle cells and neurons, although no evident association with inflammatory infiltrates has been typically found. We studied the impact of T. gondii infection on the myogenic program of mouse skeletal muscle cells (SkMC). The C2C12 murine myoblast cell line was infected with T. gondii tachyzoites (ME49 strain) for 24 hours followed by myogenic differentiation induction. T. gondii infection caused a general decrease in myotube differentiation, fusion and maturation, along with decreased expression of myosin heavy chain. The expression of Myogenic Regulatory Factors Myf5, MyoD, Mrf4 and myogenin was modulated by the infection. Infected cultures presented increased proliferation rates, as assessed by Ki67 immunostaining, whereas neither host cell lysis nor apoptosis were significantly augmented in infected dishes. Cytokine Bead Array indicated that IL-6 and MCP-1 were highly increased in the medium from infected cultures, whereas TGF-b1 was consistently decreased. Inhibition of the IL-6 receptor or supplementation with recombinant TGF-b failed to reverse the deleterious effects caused by the infection. However, conditioned medium from infected cultures inhibited myogenesis in C2C12 cells. Activation of the Wnt/b-catenin pathway was impaired in T. gondii-infected cultures. Our data indicate that T. gondii leads SkMCs to a pro-inflammatory phenotype, leaving cells unresponsive to b-catenin activation, and inhibition of the myogenic differentiation program. Such deregulation may suggest muscle atrophy and molecular mechanisms similar to those involved in myositis observed in human patients.